Feasibility of microdialysis for determination of protein binding and target site pharmacokinetics of colistin in vivo. (9th December 2014) - Matzneller, Peter; Gobin, Patrice; Lackner, Edith; Zeitlinger, Markus
Abstract Tissue pharmacokinetics and plasma protein binding of colistin have not been described in humans in vivo. Colistin concentrations in plasma, muscle, and subcutis of healthy volunteers were measured by microdialysis after a single dose of 2.5 million IU of colistin methanesulfonate. In vitro microdialysis experiments and an in vivo pilot study were performed prior to the in vivo main study. Concentration‐time profiles of total colistin in plasma were comparable with previously described values. The unbound fraction of colistin in plasma (fu) ranged from 2.8% to 14.1%. Low plasma fu correlated with low unbound colistin concentrations in muscle and subcutis. In vitro, mean relative recovery of microdialysis probes was higher in the reverse dialysis setting compared to the forward dialysis mode (71 ± 9% vs. 45 ± 14%, respectively); mean overall recovery in the main study in vivo was 49 ± 5%. Present data suggest that colistin is extensively protein bound in plasma and poorly distributed into soft tissue. However, differences in relative recovery between forward and reverse dialysis in vitro indicate that results might have been influenced by adhesion of colistin to microdialysis equipment. Microdialysis should be considered as a semiquantitative method for the estimation of unbound colistin levels in soft tissue.